Education, Girls’ Education and Climate Change - Sims, K. (Institute of Development Studies, 2021)
This Emerging Issue Report (EIR) explores research and evidence on the relationship between education, girls’ education and climate change. There is scientific consensus that climate change is real, manifested through increasing temperatures, changing rainfall patterns and increasing frequency and severity of extreme weather events, including drought, flooding and cyclones (IPCC, 2012, 2014). Climate change, environmental degradation and climate vulnerability are closely linked (IPCC, 2019). Climate change exacerbates environmental and land degradation, especially in areas with drylands and permafrost, river deltas and low-lying coastal areas. There is high confidence that people living in areas affected by environmental degradation are experiencing an increase in the negative effects of climate change (IPCC, 2019). Gender, alongside other drivers of vulnerability and exclusion, is a key determinant of an individual’s vulnerability to the effects of climate change and environmental degradation, and influences how climate change is experienced (Kwauk et al., 2019; Vincent et al., 2014; Muttarak & Lutz, 2014). It is estimated that at least 200 million adolescent girls living in the poorest communities face heightened risk from the effects of climate change (Atkinson & Bruce, 2015). Although this report refers to women and girls throughout, it is important that they are not seen as a homogenous group due to a range of factors that influence identity, including poverty, age, ethnicity, disability, socioeconomic status, geographic location and HIV status, among others (Plan International, 2011; Djoudi et al., 2016). In addition, as this report highlights, women and girls should not be seen as passive victims of climate change, as this can obscure their role as powerful agents of change and may cause misinterpretation of the causes of vulnerability (Ravera et al., 2016). Extreme weather events, such as floods and tropical cyclones, can disrupt learning in a variety of ways. The direct and immediate impacts of extreme weather include damage and/or destruction to education infrastructure; however, indirect and secondary impacts can last much longer (Kousky, 2016; Anderson, 2019). These include, but are not limited to: damage to road and transport links, obstructing access to school and learning; adolescent girls’ unwillingness to attend school if water, sanitation and hygiene (WASH) facilities are not quickly rehabilitated; inability to pay for school fees and/or learning materials; displacement of families; and reduced capacity for learning because of malnutrition or trauma (Kousky, 2016; Anderson, 2019; Nordstrom & Cotton, 2020; Chuang et al., 2018; Siriwardhana et al., 2013). Evidence and commentary on the role of education, and girls’ education, to address climate change through adaptation, resilience and mitigation is limited, albeit growing. This EIR identifies and summarises evidence and key commentary around the following themes: 1. Links between education, particularly girls’ education, and climate change. 2. How climate and environment matter for achieving gender equality. 3. Why securing girls’ education is an important strategy in addressing climate change. The EIR draws on academic research and literature from low- and middle-income countries (LMICs), as well as policy frameworks and grey literature, media articles and blogs from the climate, education and gender fields.
Keywords: _z:class:countries; evidence_review_2